2020
DOI: 10.3390/pr8050612
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toxicity on Ctenopharyngodon idella Due to Tannery Effluent Remediated by Constructed Wetland Technology

Abstract: Aquatic pollution caused by industrial effluents is an environmental issue, imposing deleterious impacts on the overall environment, specifically, on humans, by disrupting the balance of the ecosystem. Among all the industries, tanneries are considered some of the most polluting due to heavy use of toxic organic and inorganic compounds during leather processing, most of which find their way into rivers, lakes, and streams, thus exerting adverse effects on aquatic life, particularly on fish. Considering the hug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…Similarly, Nagarajan (30) found that when effluent concentrations increased, muscle tissue began to deteriorate. Many researchers have investigated the effect of various contaminants on the muscles of fish have identified histological abnormalities in the muscles of the analyzed fish (41); (42) and (36).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Nagarajan (30) found that when effluent concentrations increased, muscle tissue began to deteriorate. Many researchers have investigated the effect of various contaminants on the muscles of fish have identified histological abnormalities in the muscles of the analyzed fish (41); (42) and (36).…”
Section: Resultsmentioning
confidence: 99%
“…Fish showed more behavior changes, such as liveliness, sense of balance, opercular motion, swimming velocity, sideways movement, frontward motion with the posterior side up, and motion in a circular fashion with jerks when exposed to untreated waters (C1 and C2) as compared to the treated waters (T1 and T1*) (Table 3). Earlier studies also reported that biological treatments, including phytoremediation, reduced the toxic effects of the pollutants present in the water (Ashraf et al 2020;Shehzadi et al 2014, Tara et al 2019b). Moreover, sh showed more changed behavior in the treated water (T1*) initially having RB5 concentration of 1000 mg L − 1 as compared to the treated water (T1) initially having a concentration of 200 mg L − 1 of RB5.…”
Section: Fish Toxicity Assaymentioning
confidence: 95%
“…Toxicity of untreated and treated waters was tested using Labeo rohita (a freshwater dwelling sh) as reported earlier (Ashraf et al 2020). Treated water (twenty liters) by different treatments (C1, C2, T1, and T1*) were put in each clean glass aquarium (in triplicates), as per the experimental design.…”
Section: Plant Growth/biomass Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of oil and petroleum derivatives in many industrial sectors generates saline wastewater with high organic contaminants. Some examples of organic contaminants are phenols, aromatic hydrocarbons, nitroaromatics, and azo dyes [14].…”
Section: Introductionmentioning
confidence: 99%